Co-Benefits of Transdisciplinary Planning for Healthy Cities - Lawrence, Roderick J. (2022)
Synergies between urban planning and public health were synthesized a decade ago by the Lancet Commission’s article “Shaping Cities for Health: Complexity and the Planning of Urban Environments in the 21st Century.” Since then, innovative research projects, urban planning projects, and accumulated experience from the World Health Organization Healthy Cities project confirm that transdisciplinary contributions enable the achievement of core principles of healthy cities. This article clarifies important differences between the content, scope, and outcomes of interdisciplinary and transdisciplinary projects about public health and urban planning. It explains why transdisciplinary contributions are more likely to bridge the applicability gap between knowledge and practice in response to persistent urban health challenges; notably, they transgress the boundaries of public health and medical science; they prioritize political action in both the formal and informal construction sectors; and they include citizens, community associations, and private enterprises as partners in consortia for concerted action. This article proposes a radical shift from incremental, reactive, and corrective approaches in planning for urban health to proactive and anticipative contributions using backcasting and alternative scenarios that prioritize health. The article uses the case of public green spaces in planning for urban health. It identifies the shortcomings of many empirical studies that are meant to promote and sustain health before describing and illustrating an alternative way forward.